Enterprise JavaBeans™ component architecture designing and coding enterprise applications - Anderson, Gail 1951-; Anderson, Paul 1949- (Prentice-Hall, Inc., 2002)
This book simplifies the creation of well-designed enterprise applications using the upgraded Enterprise JavaBeans 2.0 specification. Experienced Java platform mentors Gail Anderson and Paul Anderson use detailed code examples to introduce every key skill involved in creating components, stand-alone Java platform clients, and JavaServer pages. They introduce powerful EJB platform design patterns and show how to apply them in real-world projects while avoiding critical errors in application design. Each chapter includes a "Design Guidelines and Patterns" section designed to help readers assess tradeoffs associated with design decisions, and key point summaries that tie together important concepts. In short, Anderson and Anderson give readers everything they need to build EJB 2.0 platform applications with maximum robustness, scalability, and performance.
Includes index. - Online resource; Title from title page (viewed March 11, 2002)
Keywords: JavaBeans; Java (Computer program language); Java (Langage de programmation); Engineering & Applied Sciences; Computer Science